Opredeljajuscie napravlenija naucnych issledovanij i puti razvitija sportivnoj mediziny vo VNIIFKe - Graevskaya, N. D.; Iordanskaya, F. A. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
Among many aspects of scientific activity of All-Russia scientific research institute of physical culture the problems of sports medicine always had the big densities. Their becoming and development are closely connected to the history of institute. It is difficult to list these many-sided problems worked by those scientists within 70 years of existence of institute. Before sports medicine are rather serious and crucial tasks. The successful solving of them determines the health, physical condition, life expectancy of the population of Russia and successes of the Russian sports stands in many respects today. It demands to increase the efficiency of researches, the consolidation of forces, equipment, personnel and restoration of the role of the institute as the coordinating center on problems of sports medicine.